Late Pleistocene and Holocene Lithic Variability at Goda Buticha (Southeastern Ethiopia): Implications for the Understanding of the Middle and Late Stone Age of the Horn of Africa - (:unkn) unknown (My University, 2017)
Abstracts The Late Pleistocene is a key period to understand the shift from the Middle ( msa ) to the Late Stone Age ( lsa ) in Africa. More generally, it is also a crucial time for elucidation of changes in the technological behaviours of human populations in Africa after the main Out of Africa event of modern humans ca. 60-50 thousand years ago. However, the archaeological record for this period is relatively poor, particularly for the Horn of Africa. Here we present a detailed analysis of the lithic assemblages from Goda Buticha ( gb ), a cave in southeastern Ethiopia, which has yielded a long stratigraphic sequence including Late Pleistocene and Holocene levels. This study (1) contributes to a better knowledge of the late msa in the Horn of Africa; (2) documents a late Holocene lsa level ( gb – Complex i ); (3) highlights the presence of msa characteristics associated with lsa features in the Holocene ( gb – Layer ii c). This adds to the emerging record of great lithic technological variability during the Late Pleistocene and Holocene in this region.
Keywords: African Research